Thai Language Learning Management for Muslim Student in Islamic Private Schools of Southern Thailand - สองเมือง, จารุวัจน์; หะยีสะมะแอ, ซอลีฮะห์; ไวยวรรณจิตร, สุรชัย; หะยีสาอิ, อิบรอเฮม; บากา, มูหามัดรูยานี (Al-HIKMAH Journal, 2018)
The present study is a qualitative research. The purposes of this research are: 1) to examine the problems of the Thai language instruction management in Islamic private schools in Southern Thailand, 2) to explore the opinion of school administrators and teachers on guidelines of instruction management based on the second language learning methods. The research methods used in the study are interviews, focus group discussions and a seminar. The key informants are composed of 20 school administrators and 40 teachers from Islamic private schools in Southern Thailand. The study reveals the following results: 1) The schools always have to suffer changing workforce and instability in the positions of Thai language teachers. 2) The teachers who are to teach in Thai language classes are not graduates from the Thai language major. 3) The Thai language teachers have only 1-3 year experience in teaching. 4) The majority of the key informants were fairly satisfied with the achievement of the Thai language teaching. However, the teaching of Thai language needs further improvement and preparation for the changes to come. 5) The students have more learning experience in Thai language before they are enrolled into the schools than before. This is because the social conditions in the southern provinces is getting more open to Thai language in which Bangkok-based mass media plays a significant role in creating Thai language friendly environment. The study also shows that the lack of teaching skills and proper learning management affected adversely the way in which those teachers conduct the classes and design instruction media for students with different backgrounds and experiences. The key informants propose a development model of Thai language learning for the local students which consists of three aspects. They are: 1) development of integrated learning units, especially by integration of religious knowledge and the local culture, 2) learning activities designed to be conducted in consistence with the student learning style and teaching methods of Thai language as a second language, and 3) development of the learning materials based on the religious values and local culture of the people.